What matters in disclosures of key audit matters: Evidence from Europe. (23rd December 2018) - Pinto, Inês; Morais, Ana Isabel
Abstract: New regulation in the European Union has introduced the mandatory disclosure of key audit matters (KAMs) to audit reports. The EU has identified KAMs as significant risks, significant transactions or events, or significant judgments by auditors. This paper aims to determine the factors that influence the number of KAMs that auditors disclose in the main European countries under the new regulation. We predict that the litigation risk, reputation loss, auditor–client relationship, precision of accounting standards, and the effect of regulators and supervisors' activities affect the number of KAMs that auditors disclose. The sample consists of firms on the FTSE 100, CAC 40, or AEX 25 that have disclosed KAMs at the 2016 fiscal year‐end. In line with our hypotheses, the findings show that a higher number of business segments (complexity) and more precise accounting standards lead to the disclosure of a higher number of KAMs. Contrary to our expectations, the results indicate that a positive association exists between the audit fee and the number of KAMs disclosed. As audit fees can be related to higher client risk, this finding could indicate that litigation risk dominates any auditor–client dependence. Further, although auditors often view their audits of banks as complex, the findings show a negative association between banks and the number of disclosed KAMs. This evidence may be related to the fact that financial institutions are in a highly regulated and supervised industry that reduces the need to disclose the KAMs.